Prevalence of traumatized permanent incisors among Yemeni children - A. AL-Jawfi, Khaled (International Journal of Dental Research, 2018)
Objective: This study was designed to determine the prevalence and identify the causes of traumatized permanent incisors among Yemeni children.Patients and Methods: This study was conducted on five hundreds Yemeni children, (250) boys and (250) girls with an age ranged from 8 -12 years. The sample was collected from pediatric dental clinics, College of Dentistry, University of Sciences & Technology, Sana'a, Yemen.Results: In the total sample of 500 child, 36 traumatized cases with a prevalence of 7.2%. Regarding to the gender, the prevalence of traumatized cases was found in boys (9.6%) more than girls (4.8%) with a ratio of 2:1. Regarding to location of trauma, the maxillary central incisors were the highest traumatized cases (86.1%). Regarding to type of trauma, untreated dental fracture was the highest prevalence (58.3%) of all traumatized cases for both genders and excluded tooth was the lowest prevalence (2.8%). Regarding to cause of trauma, traumatized cases due to fall were the highest prevalence (58.3%) for both genders, then due to violence were (25%), and due to road traffic accident were the lowest prevalence (16.7%) Conclusion: Based on the study results, the prevalence of traumatized permanent incisors was seen in 7.2% of Yemeni children and frequented in boys more than girls with a ratio 2:1. The maxillary central incisors were the most frequently affected teeth by trauma (86.1%) of permanent incisor teeth and fall (58.3%) was the main cause of traumatized cases.